Science literacy, critical thinking skill, and motivation: A correlational study - Rosita Primasari; Mieke Miarsyah; R. Rusdi (University of Muhammadiyah Malang, 2020)
Scientific literacy and critical thinking skill are the considerable 21st century competencies must be owned by nowadays students. This study aimed at determining the correlation among three variables i.e. critical thinking skill, motivation, and scientific literacy possessed by high school students. The research used a quantitative approach to explore the correlation among variables observed. The total sample were 124 of X MIPA graders selected using the simple random sampling technique. The data collection was carried out by providing test instruments to measure students’ critical thinking skill, motivation, and scientific literacy. The all variables then were analyzed using multiple linear regression. The results showed that (1) there was a positive correlation between the critical thinking skill and scientific literacy (11.83%), (2) there was no significant correlation between motivation and scientific literacy, and (3) the both predictors (i.e. critical thinking skill and motivation) were able to predict the criterion (scientific literacy) (22.56%). It is suggested to optimize students’ critical thinking skill and motivation to sharpen students’ scientific literacy.